2021
DOI: 10.34257/gjmbravol21is2pg21
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Leadership Style and Public Participation in the County Governments in Kenya

Abstract: Purpose: The purpose of this study was to determine the influence of transformational leadership style on public participation in the county governments in Kenya. Methodology: The study adopted both descriptive and explanatory research designs. The study population comprised citizens who are registered voters in all the 47 counties in Kenya. A two stage sampling technique was used to select 8 counties and a sample of 400 respondents to participate in the study. A pilot test was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…Participants agreed that leaders should delegate tasks to employees arguing that the practice strengthened their team relationships, enabled them to develop new skills and capabilities and increased trust in the team leader. As observed by Njiiri et al (2021), leader-team trusts as key to strengthening team capabilities and commitment towards team goals. Northouse (2019) stated that delegation and valuing member input in organizations were essential management skills that allowed leaders to ~ 155 ~ develop individual and collective team capabilities to improve team productivity and efficiency.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Participants agreed that leaders should delegate tasks to employees arguing that the practice strengthened their team relationships, enabled them to develop new skills and capabilities and increased trust in the team leader. As observed by Njiiri et al (2021), leader-team trusts as key to strengthening team capabilities and commitment towards team goals. Northouse (2019) stated that delegation and valuing member input in organizations were essential management skills that allowed leaders to ~ 155 ~ develop individual and collective team capabilities to improve team productivity and efficiency.…”
Section: Discussionmentioning
confidence: 90%
“…Research has argued that maintaining attention and listening to employees influences credibility and trust and stimulates commitment to team goals. In Njiiri et al (2021) it was suggested that empowering employees involved entrusting power to them, paying attention to their needs and performance, and affective listening to their ideas, opinions and solutions to problems. Further, this is linked to team performance.…”
Section: Introductionmentioning
confidence: 99%
“…This leadership style is also considered to be effective in empowering individuals who are given opportunity of performing their duties in an autonomous way thus enhancing learning and inspiration that assist followers in stimulating organizational performance (Rawashdeh et al, 2020). According to Njiiri et al (2021), transformational leadership is composed of four main elements which include idealized influence or the charisma, inspirational motivation, intellectual stimulation and individualized consideration. All the four elements individually or combined do influence level of performance whether at individual or organizational level.…”
Section: Transformational Leadershipmentioning
confidence: 99%